PASTRY NAMES RELATED TO ENGLISH AND UZBEK FOLK CEREMONIES (Intent Research Scientific Journal, 2023)
This article is about pastry names related to English and Uzbek folk ceremonies. Names of confectionery related to English and Uzbek folk rituals are compared.